The moderating effect of board homogeneity on the relationship between intellectual capital disclosure and corporate market value of listed firms in Nigeria - Anifowose, Mutalib; Abdul Rashid, Hafiz Majdi; Annuar, Hairul Azlan (IIUM Press, International Islamic University Malaysia, 2017)
This paper examines whether or not concentration of board members based on ethnicity and religion can impact on intellectual capital disclosure and thereby influence the corporate market value in Nigeria. This article reports the results from a two-step dynamic system generalized method of moment estimation based on 455 firm-year observations from 91 listed firms on the main board of the Nigeria Stock Market for the period 2010-2014. The study measures board homogeneity based on religious and ethnic affiliations of corporate board members in line with upper echelons theory in explaining their moderating effect on the relationship between intellectual capital disclosure and firm value which is proxied by cost of capital and share price volatility. The empirical results indicate that board ethnic and religious composition has moderating effect on the relationship between intellectual capital disclosure and cost of corporate market value. Though the finding might not be extended to smaller firms which could be a limitation, the results of this study are useful to all stakeholders especially the financial reporting council of Nigeria in policy formulation and perhaps issuance of corporate governance standard that would provide a more diversified board than currently being practiced in the country among the larger firms. The study is the first to consider moderating effect of religious and ethnic composition on the relationship between intellectual capital (IC) disclosure and corporate market as well as controls for heteroscedasticity and endogeneity issues by adopting two-step system generalized method of moments as a parameter estimator.